CRISPR/Cas-9 vector system: targets UL-39 and inhibits Simplexvirus humanalpha1 (HSV-1) replication in vitro: CRISPR/Cas-9 vector system inhibits HSV-1 replication in vitro - Vasques Raposo, Jéssica; Rodrigues Carvalho Barros , Luciana; Ribas Torres, Lauana; Barbosa da Silva Pinto , Rafaela; de Oliveira Lopes , Amanda; Mello de Souza , Elen; Hernan Bonamino , Martin; Salete de Paula, Vanessa (Cellular and Molecular Biology, 2023)
Simplexvirus humanalpha1 (HSV-1) aﬀects approximately 67% of the world's population. Here, we sought to use the CRISPR / Cas9 system with the UL39 target, essential for virus replication. The sgRNA sequence was inserted into the plasmid (PX459-UL39). Vero cells were transfected with PX459-UL39, and inhibition of viral replication was assessed 24 and 48 hours later using plaque assays and ﬂuorescence and qPCR. Fluorescence analyses revealed the presence of anti-HSV-1 CRISPR/Cas9 within Vero cells, and qPCR showed that the viral load decreased by> 95% of cells transfected with anti-HSV-1 CRISPR / Cas 9. Our data demonstrate the usefulness of the PX459-UL39 to inhibit HSV-1 infection.